Untargeted mass spectrometry discloses plasma solute levels poorly controlled by hemodialysis - Sirich, Tammy L. (PLoS One, 2017)
Many solutes have been reported to remain at higher plasma levels relative to normal than the standard index solute urea in hemodialysis patients. Untargeted mass spectrometry was employed to compare solute levels in plasma and plasma ultrafiltrate of hemodialysis patients and normal subjects. Quantitative assays were employed to check the accuracy of untargeted results for selected solutes and additional measurements were made in dialysate and urine to estimate solute clearances and production. Comparison of peak areas indicated that many solutes accumulated to high levels in hemodialysis patients, with average peak areas in plasma ultrafiltrate of dialysis patients being more than 100 times greater than those in normals for 123 features. Most of these mass spectrometric features were identified only by their mass values. Untargeted analysis correctly ranked the accumulation of 5 solutes which were quantitatively assayed but tended to overestimate its extent. Mathematical modeling showed that the elevation of plasma levels for these solutes could be accounted for by a low dialytic to native kidney clearance ratio and a high dialytic clearance relative to the volume of the accessible compartment. Numerous solutes accumulate to high levels in hemodialysis patients because dialysis does not replicate the clearance provided by the native kidney. Many of these solutes remain to be chemically identified and their pathogenic potential elucidated.